The Effects of Self-Efficacy, Organizational Commitment, and Work-Life Balance on Employee Job Satisfaction at Mars City Hotel - I Gede Agus Wiadnyana; Putu Agus Eka Rismawan; I Komang Suryadnya Diputra; I Kadek Andika Budi Utama (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
Human resources play a strategic role in a company’s success. This study aims to examine the influence of self-efficacy, organizational commitment, and work-life balance on employee job satisfaction at Mars City Hotel. The study was conducted at Mars City Hotel, located at Jalan Kertha Dalem, Sidakarya Village, South Denpasar District, Denpasar City, Bali. All 34 employees served as respondents using a saturated sampling technique. Data were collected through observation, interviews, documentation, and the distribution of questionnaires. The analytical techniques used included descriptive analysis and inferential analysis, specifically multiple linear regression, classical assumption tests, the coefficient of determination, the F-test, and the t-test to determine the influence of each independent variable on job satisfaction. The results of the analysis indicate that self-efficacy, organizational commitment, and work-life balance have a positive and significant influence on employee job satisfaction at Mars City Hotel. This implies that improvements in these three variables will lead to an increase in employees’ job satisfaction levels.